2013
DOI: 10.3141/2396-13
|View full text |Cite
|
Sign up to set email alerts
|

Impacts to Transit from Variably Priced Toll Lanes

Abstract: This paper describes the impacts on transit performance from three separate conversions of high-occupancy vehicle lanes into variably priced high-occupancy toll (HOT) lanes in Miami, Florida; Minneapolis, Minnesota; and Atlanta, Georgia. The data showed that the conversions had no negative impact on bus performance. In all three cities, the buses experienced travel time savings after the conversion: 17 min in Miami, 4.5 min in Minneapolis, and 5 min in Atlanta. Similarly, the HOT conversions did not negatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…One of the potential impacts identified is a change in transit ridership. Previous studies demonstrated that not a small portion of new bus riders in HOT lane corridors (for example, 23% in Minneapolis and 53% in Miami) were influenced to take transit by HOT lanes, resulting in an increase in transit ridership (Pessaro, Turnbull, & Zimmerman, 2013). However, the bus ridership increase seems not to be always guaranteed by the introduction of HOT lanes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the potential impacts identified is a change in transit ridership. Previous studies demonstrated that not a small portion of new bus riders in HOT lane corridors (for example, 23% in Minneapolis and 53% in Miami) were influenced to take transit by HOT lanes, resulting in an increase in transit ridership (Pessaro, Turnbull, & Zimmerman, 2013). However, the bus ridership increase seems not to be always guaranteed by the introduction of HOT lanes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Minneapolis, it was 23 percent. In Atlanta, it was 45 percent (Pessaro, Turnbull, & Zimmerman, 2013).…”
Section: Table 2-1 Hov Toll Policies On Hot Lanesmentioning
confidence: 99%